2015
DOI: 10.1016/j.msea.2014.12.045
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of small punch creep behaviour in the γ titanium aluminide Ti–45Al–2Mn–2Nb

Abstract: a b s t r a c tPrevious literature on gamma titanium alumindes (γ-TiAl) have found that this family of alloys offer significant potential for replacing more conventional nickel and titanium based alloy systems in future designs of gas turbine engines. Despite the inherent brittle nature of such materials, γ-TiAl typically exhibits considerable ductility at elevated temperatures and a demonstrable uniaxial creep response. Until now, the creep properties of γ-TiAl have primarily been sourced from conventional un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 17 publications
1
22
0
Order By: Relevance
“…To date these methods have largely been adopted to characterise the creep [3], [4], tensile [5], [6] and fracture characteristics [7], [8] of numerous material systems [9], [10] from a range of industrial applications for sampling [11], [12]. This paper will now detail the research undertaken in realising a small-scale test methodology capable of characterising the localised fatigue properties of ALM built structures.…”
Section: Introductionmentioning
confidence: 99%
“…To date these methods have largely been adopted to characterise the creep [3], [4], tensile [5], [6] and fracture characteristics [7], [8] of numerous material systems [9], [10] from a range of industrial applications for sampling [11], [12]. This paper will now detail the research undertaken in realising a small-scale test methodology capable of characterising the localised fatigue properties of ALM built structures.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research [13,23] has demonstrated that the shape of the time displacement/deflection curves from SP creep tests are qualitatively similar and representative of the shape typically observed from uniaxial testing approaches. Now, over recent years, many researchers and scientists have devoted significant effort in establishing a series of correlative means capable of comparing the results obtained from SP creep testing to data gathered from more traditional creep testing methodologies.…”
Section: Data Interpretation and Correlations To Uniaxial Creep Resultsmentioning
confidence: 54%
“…In contrast, SP testing has also been employed to characterise the creep properties of more inherently brittle type materials, such as γTiAl [23] or Mg alloys [24]. Figure 9 presents the typical fracture morphology for a brittle small punch disc.…”
Section: Fractographymentioning
confidence: 99%
See 2 more Smart Citations